DEVELOPMENT OF VERTICAL CULTURE CULTIVATION IN THE MUHAMMADIYAH STUDENT ASSOCIATION OF CANDI - Abror, M.; Miftakhurrohmat, A.; Prihatiningrum, Andriani Eko; Eviyanti, Ade (Journal of Social Comunity Services, 2024)
General Background: Food security and independence are critical issues in urban environments, where limited land poses challenges for traditional agriculture. Specific Background: Vertical culture cultivation has emerged as a potential solution to optimize narrow land for agricultural purposes, but its application remains underutilized in many communities. Knowledge Gap: While many individuals possess basic agricultural knowledge, there is limited familiarity with vertical culture systems, particularly among youth organizations such as the Muhammadiyah Student Association (IPM) in Candi District. Aims: This community service program aimed to improve participants' understanding and skills in vertical culture cultivation to support food independence on narrow land. Results: Through a structured process of socialization, training, and mentoring, participants gained the ability to design and implement vertical culture systems, leading to improved agricultural productivity in terms of both quantity and quality of harvests. The program's evaluation showed a significant increase in participant knowledge and the successful adoption of vertical farming techniques. Novelty: This program uniquely demonstrates the integration of technology and sustainable practices in vertical cultivation, providing a practical and scalable model for urban agriculture. Implications: The success of this initiative highlights the potential for vertical culture cultivation to contribute to food security in urban areas, with opportunities for further development through continuous innovation and broader community engagement. This program serves as a blueprint for future urban agricultural efforts, offering a sustainable approach to maximizing the use of narrow land in densely populated regions.